Imam al-Bukhari and the transmission of prophetic knowledge: the role of the Imam Bukhari international scientific research centre in Samarkand - Abd Rahman, Shukran; Ziyodov, Shovosil (Human Assistance & Development International Inc. (HADI Inc.), 2025)
Abu ʿAbdallāh Muḥammad ibn Ismāʿīl al-Bukhārī, or Imam al-Bukahri, was born in 194 AH (809/810 CE) in the city of Bukhara, in present-day Uzbekistan. He came from a Persian family that had embraced Islam three generations before his birth. His father passed away when he was still an infant, leaving his upbringing in the care of his mother. Since his childhood, Imam al- Bukhari displayed remarkable dedication to learning. He studied under local scholars, immersing himself in the sciences of hadith and Islamic jurisprudence (fiqh). In his late teens, al-Bukhari traveled to Makkah with his mother and brother to perform the Hajj. Al-Bukhari remained in Makkah and Madinah for several years, where he learnt from some of the most eminent scholars of the time. He memorized both the texts (matn) and the chains of narration of hadith, while also mastering ʿilm al-rijāl, or the discipline concerned with evaluating the reliability of narrators.